The supportive care needs of Iranian couples during postpartum hospitalization: A protocol of design, implementation and evaluation of intervention - Zahra Rastad; Shirin Shahbazi Sighaldeh; Zahra Behboodi Moghadam; Shahla Faal Siahkal; Elham Ebrahimi (PLoS ONE, 2026)
Background The immediate postpartum period is marked by significant physiological and hormonal changes, which may present mothers with various social, emotional, and functional challenges. The goal of optimal postpartum hospice care is to sustain and enhance the health of both mothers and newborns while fostering a supportive environment for families and communities to address diverse health and social needs. Implementing comprehensive supportive care programs that offer full coverage of services for women can ensure that their needs are adequately met during this critical postpartum phase. Consequently, this study aims to investigate the supportive care requirements of couples during the postpartum period using a mixed-methods approach, along with the design and implementation of a needs-based intervention to improve health services during this essential time. Methods This study employs a multistage mixed-methods approach, structured in a sequential exploratory design consisting of three distinct phases. Initially, an exploratory qualitative study will be conducted utilizing a conventional content analysis framework to investigate the supportive care needs of couples during the postpartum hospitalization period. The second phase will involve a nominal group meeting in which the concerns and supportive care requirements identified by couples will be discussed in the presence of reproductive health specialists, policymakers, and experts. This collaborative effort will facilitate the prioritization of these needs. Following this prioritization, a comprehensive review of interventions and programs addressing couples’ supportive care needs during the postpartum hospitalization period on a global scale will be undertaken. Finally, after another panel of experts, the best intervention in this regard will be designed and consisted of a quantitative clinical trial aimed at evaluating the effectiveness of the intervention on the supportive care needs of Iranian couples during the postpartum period. Discussion The results of this study can lead to the design of a comprehensive supportive care program with comprehensive coverage of couples’ needs during the postpartum hospitalization period. The study aims to ensure that couples’ needs are met in this critical period. If this program is effective, it can be included in postpartum health care guidelines. Clinical trial registration No. IRCT20110621006854N8 (2024-11-16)